ICT innovation and economic development: lessons from a tech start-up in Soweto - Masango, Collen (My University, 2017)
Twenty three years into democratic South Africa, the country’s largest and most famous township, Soweto, is still the unfortunate epitome of economic marginalisation and poverty; a reflection of the unrelenting effects of apartheid spatial planning and the exclusion of black people from mainstream economy. Contemporary development discourse centres on sustainability, innovation and smart city concepts, as some of the key influencers. Specifically ICTs are viewed as enablers of economic development, capable of disrupting entrenched systems and economies. This research explores the opportunities presented by ICT innovation for economic development amongst small businesses operating in Soweto, Johannesburg. The research hones in on ICT4D, a concept of development centred on ICTs to uncover development planning interventions and principles, applicable to the South African context. Using the experiences of a Soweto based Start-up Company, iTea; the research explores the diffusion of their Township Economy App, its rate of adoption by these businesses and its economic impact. Key lessons for local authorities such as Johannesburg is the need to harness local content and innovations, derived from tech start-ups and innovators who live in those communities in order to achieve local economic development.
Research report presented for a Masters Degree in Development Planning in the Faculty of Engineering, School of Architecture and Planning, University of the Witwatersrand, December, 2017
Keywords: Information technology--Economic aspects--South Africa; Economic development--South Africa